مهارات التفكير التحليلي ومدى توافرها لدى تلاميذ المرحلة الابتدائية - محمد، أسماء فرحات حسن; عبدالقادر، عبدالرازق مختار محمود; علام، صابر علام عثمان (جامعة أسيوط - كلية التربية - مركز تعليم الكبار, 2024)
استهدف البحث الحالي تحديد مهارات التفكير التحليلي والوقوف على مدى توافرها لدى تلاميذ الصف السادس الابتدائي، واعتمد لهذا الغرض المنهج التجريبي، باستخدام التصميم شبه التجريبي ذي المجموعة الواحدة عند إجراء تجربة البحث وتطبيق أدواته، وتم إعداد قائمة بمهارات التفكير التحليلي شملت (۲۰) مهارة، وتم إعداد اختبار لقياس هذه المهارات، وطبق البحث على مجموعة من تلاميذ الصف السادس الابتدائي مكونة من (۳۰) تلميذا وتلميذة بمدرسة أبنوب الابتدائية الجديدة التابعة لإدارة أبنوب التعليمية، بمحافظة أسيوط. وبتطبيق الاختبار المعد على مجموعة البحث، اتضح ضعف مستويات التلاميذ في مهارات التفكير التحليلي المحددة في البحث؛ لذا يوصي البحث بضرورة الاهتمام بتنمية مهارات التفكير التحليلي لدى التلاميذ بمختلف المراحل الدراسية، وتلاميذ الصف السادس الابتدائي خاصة، واستخدام الأساليب والاستراتيجيات التدريسية لهذا الهدف، والإفادة من أدوات البحث في العملية التعليمية، كما قدم البحث مجموعة من المقترحات المرتبطة بما تم التوصل إليه من نتائج. The current research aimed to identify analytical thinking skills, and their availability among sixth grade students. The research followed the experimental method using a one-group quasi-experimental design. The research group affiliated with one group, when conducting the research experiment and applying its tools; a list of analytical thinking skills, amounting to (20) skills, testing analytical thinking skills, and the research was applied to a group of (30) students from the New Abnoub Primary School, the Abnoub Educational Administration in Assiut Governorate. By applying the prepared test to the research group, it became clear that the students’ poor levels of analytical thinking skills identified in the research. Therefore, the research recommends the need to pay attention to developing analytical thinking skills among students at various educational levels, and sixth grade students in particular, and to use teaching methods and strategies for this goal, and to benefit from research tools in the educational process. The research also presented a set of proposals related to what was reached. Of the results.
Keywords: مهارات التفكير -- العملية التعليمية -- طلبة المدارس -- المرحلة الابتدائية